2019
DOI: 10.20546/ijcmas.2019.812.072
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Effect of Pyrimethamine-Loaded Niosomes in the Treatment of Acute Toxoplasmosis

Abstract: Toxoplasma gondii infection has a worldwide distribution. Pyrimethamine (PYR) is the most effective drug for treatment of toxoplasmosis. Unfortunately, it has low oral bioavailability which requires an increase in the dose that results in increased its side effects. Nanostructures showed promising potential to overcome this problem. This study aimed to evaluate the effect of intraperitoneal injection (IP) of PYR-loaded niosomes compared to PYR in the treatment of acute toxoplasmosis in experimentally infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This superior response could reflect two factors: firstly, the colloidal nature of the niosomes could enhance the MQ bioavailability or its distribution to the mice tissues (Olivera et al, 2013), and secondly, the relatively high ability of the niosomes to provide a transport medium for lipophilic drugs, such as MQ (Mourao et al, 2005). Similarly, El-Mansory et al (2019) found that niosomal-PYR significantly increased the survival rate of mice when compared with PYR alone. Additionally, these results agree with that documented in previous studies which evidenced that the use of nanosystems enhanced the efficacy of anti-toxoplasmic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This superior response could reflect two factors: firstly, the colloidal nature of the niosomes could enhance the MQ bioavailability or its distribution to the mice tissues (Olivera et al, 2013), and secondly, the relatively high ability of the niosomes to provide a transport medium for lipophilic drugs, such as MQ (Mourao et al, 2005). Similarly, El-Mansory et al (2019) found that niosomal-PYR significantly increased the survival rate of mice when compared with PYR alone. Additionally, these results agree with that documented in previous studies which evidenced that the use of nanosystems enhanced the efficacy of anti-toxoplasmic drugs.…”
Section: Discussionmentioning
confidence: 99%